Impacts of AIOT Implementation Course on the Learning Outcomes of Senior High School Students - Chih-Cheng Tsai; Yuh-Min Cheng; Yu-Shan Tsai; Shi-Jer Lou (MDPI AG, 2021)
In this study, experimental teaching was conducted through the artificial intelligence of things (AIOT) practical course, and the 4D (discover, define, develop, deliver) double diamond shape was used to design the course and plan the teaching content to observe the students' self-efficacy and learning anxiety. The technology acceptance model (TAM) concept was used to explore learning effectiveness and satisfaction. A total of 36 Senior One students from a senior high school in Kaohsiung were selected as the research subjects in two classes per week for 13 weeks. Questionnaires and qualitative interviews were used to understand the correlation between students' self-efficacy, anxiety, outcomes, and learning satisfaction with the AIOT course during the flipped learning process. The study used SmartPLS3 to analyze the measurement model and structural model, and bootstrapping to conduct the path analysis and validate the research hypotheses. Because this research provides students with relevant online teaching videos for linking and browsing in the textbooks, and the video time should not be too long, in the teaching process, small-scale online learning courses are adopted for flipped teaching, which promptly arouses students' interest and enhances their learning participation. Through the sharing of homework with each other, its content deficiencies were modified, students' anxiety in learning was reduced, and the effect of learning and thinking together was achieved; in the teaching mode, theoretical content was combined with physical and practical courses to implement cross-disciplinary. To learn, the principle of 4D double diamond design to make "reciprocal corrections" between curriculum planning and teaching implementation as the teaching model framework was used. The results of this study show "self-efficacy" has a significant positive effect on the "perceived usefulness" and "perceived ease of use" of users. "Learning anxiety" does not significantly predict the "perceived ease of use" or "perceived usefulness" of flipped learning using online e-learning. The "perceived ease of use" and "perceived usefulness" have positive impacts on the prediction of "behavioral intention" in flipped teaching using online digital teaching materials. The "perceived ease of use" has a positive and high impact on "perceived usefulness". "Learning engagement" positively affects students' actual "behavioral intention" towards learning. Students are highly receptive to learning new knowledge about science and technology.